2021
DOI: 10.3390/ijerph18179011
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Status May Associate Different Risk(s) with Early Childhood Caries (ECC) That Can Cause the Development of Psychomotor Deficiency in Preschool Children Aged 3–6 Years Old: The Results of Preliminary Analysis from a Cohort Study

Abstract: Background: We have recently shown that there is a positive correlation between severe caries and developing psychomotor deficiency in preschool children. To fully re-assess such a relationship, we embarked on a 3-year longitudinal follow-up study of kindergarteners, where we aimed to: (i) confirm whether early childhood caries is causally related to the development of psychomotor deficiency as proposed, and (ii) address any significant role or contribution of socio-economic status associated with caries–psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(31 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…However, others in the field have shown that SES has long been considered one of the risk factors, or even a predictor, for ECC development and/or progression in children, including levels of family income, parental education and occupation, and access to medical/dental healthcare facilities, etc., all of which may be attributed to the equity issue of caries distribution in the population studied [ 15 , 16 , 17 , 19 , 20 , 22 , 23 , 24 , 25 , 32 ]. Interestingly, such intricate causal interactions between ECC and developing the psychomotor deficiency described above are found to be further implicated by other non-biologic risks/determinants, including SES (especially maternal educations), family-income level, and the frequency of dental visits, which have all been reported in our recent preliminary analyses [ 21 ].…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…However, others in the field have shown that SES has long been considered one of the risk factors, or even a predictor, for ECC development and/or progression in children, including levels of family income, parental education and occupation, and access to medical/dental healthcare facilities, etc., all of which may be attributed to the equity issue of caries distribution in the population studied [ 15 , 16 , 17 , 19 , 20 , 22 , 23 , 24 , 25 , 32 ]. Interestingly, such intricate causal interactions between ECC and developing the psychomotor deficiency described above are found to be further implicated by other non-biologic risks/determinants, including SES (especially maternal educations), family-income level, and the frequency of dental visits, which have all been reported in our recent preliminary analyses [ 21 ].…”
Section: Introductionmentioning
confidence: 62%
“…To study the causal interactions addressed above, we have designed a three-year longitudinal study via the random recruitment of children aged three to six years old, whose baseline vs. follow-up caries activities and their growth-and-development aspects were collected via standardized protocols from randomly selected central and southern regions of Taiwan. Based on our recent reports [ 13 , 14 ], the protocols employed for the current study were directed via the same measures and criteria previously established [ 18 , 21 ], which are described below regarding their capacity to achieve the objectives stated above. After obtaining legal consent, the caries/dmft measures, as independent variables; the demographic data of age, gender, and BMI (height/weight); and the amended comprehensive scales (CCDI-aspects as the dependent variable) regarding psychomotor development, parental educations vs. occupations, and dietary information by categories were collected for the calculation of their inter-relationships.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations